ダイ31ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1989–1990 - 佐野, 雅史; サノ, マサシ; Sano, Masashi (1996)
P(論文) 第31次南極地域観測隊は, 隊長内藤靖彦以下55名で編成された。このうち昭和基地の越冬隊は内藤靖彦以下30名, あすか観測拠点の越冬隊は白石和行越冬副隊長以下8名である。夏隊は, 副隊長佐野雅史以下17名で編成され, 南極条約に基づく交換科学者として, 中国から2名, ベルギーから2名が同行した。1989年11月14日東京港を出港した「しらせ」は, オーストラリアのフリーマントル港に寄港したのち, 12月17日ブライド湾に到着した。あすか観測拠点での越冬用物資および小型ヘリコプター2機を含むセールロンダーネ山地での地学・生物・雪氷用機材173トンを揚陸したのち, 越冬隊員8名と夏期調査隊員(交換科学者2名を含む)14名を残し, 12月30日昭和基地に向かった。リュツォ・ホルム湾の例年にない厳しい氷状に砕氷航行は難航し, 昭和基地には1990年1月14日に到着, 輸送(624トン), 建設作業, 野外調査等を1月31日まで行い, 2月1日には越冬を交代し, 同日ふたたびブライド湾に向かった。2月7日ブライド湾に到着し, 9日までの間に小型ヘリコプター2機とセールロンダーネ山地調査隊の収容, 海洋観測係留ブイの設置を行った。隊独自では初めてのヘリコプターの運用を行い, セールロンダーネ山地全域の77カ所に着陸し, 山岳域の調査に威力を発揮した。2月12日から19日にかけてアムンゼン湾沿岸露岩域の地学・生物の調査を行ったのち, 海洋観測を実施しながら東航し, 3月21日オーストラリアのシドニー港に入港した。観測隊員は, 空路にて3月28日に成田に, 「しらせ」は4月13日に東京港に帰着した。 The 31st Antarctic Research Expedition (JARE) consisted of 55 members, of which the 30 members of the wintering party at Syowa Station were led by Y. NAITO, 8 members of the wintering party at Asuka Station by K. SHIRAISHI and 17 members of the summer party by M. SANO. In addition, two Chinese scientists and two Belgian scientists participated. The icebreaker SHIRASE, leaving Tokyo on 14 November 1989,after calling at Fremantle, Western Australia, arrived at Breid Bay on 17 December. The helicopter and surface transportation of 173t of cago including two AS-350 helicopters, 8 wintering members and 14 members of the summer SΦr Rondane Mountains expedition from the ship to Asuka Station were completed by 30 December. The ship reached Syowa Station on 14 January 1990,it needed 15 days to approach Syowa Station because the pack ice and first ice in Lutzow-Holm Bay were very thick and heavy compared with a normal year. Unloading of 624t of the cargo, and the summer operations including field research work, relief of the observation team, and construction and renewal of some facilities were completedby 31 January 1990. The SHIRASE left Syowa Station 1 February and arrived again at Breid Bay on 7 February, and picked up the field party and two AS-350 helicopters. On the way from Breid Bay to Sydney, Australia, the ...